La (im)potencia del derecho frente a la corrupción - Bueno Ochoa, Luis (2025)
This study on corruption begins by contextualising and offering definitions of a complex and multifaceted phenomenon in which ethics, politics and law converge. After considering the possibility of a new right to a corruption-free society, the regulation of transparency and the fight against corruption itself is addressed, mainly from the point of view of the Spanish legal system. The invisible transparency and the apparent fight against corruption give way to two forms of perception of the Law in the fight against corruption. The power and powerlessness of the Law thus turn out to be much less at odds with each other than one might at first assume. Finally, it is insisted not only that corruption and democracy areincompatible, but also that the fight against corruption has Civic Education as its corollary in the face of the unavoidable need to consider preventing it and combating it culturally.